IMPLEMENTATION of GOVERNMENT POLICIES at THE BINA MARGA CIPTA KARYA AND SPATIAL PLANNING OFFICE (A CASE STUDY of ROAD INFRASTRUCTURE DEVELOPMENT IN THE LEMBANG SUB-DISTRICT OF PINRANG DISTRICT) - Isnah Kharina; Andi Aslinda; Andi Cudai Nur; Aiman Sabar Rezky (Universitas Negeri Makassar, 2026)
This research aims to determine the implementation of Road Infrastructure Development Policy in Lembang District. This research includes qualitative research with descriptive research type. Data collection was used using interview, observation and documentation techniques. The data obtained from the research results were processed using data analysis according to Miles & Huberman, namely data condensation, data presentation, drawing conclusions and verification. The results of the research show that the implementation of government policy at the Bina Marga Cipta Karya and Spatial Planning Service (Case Study of Road Infrastructure Development in Lembang District, Pinrang Regency) can be said to have run smoothly in terms of standard indicators and policy targets, resources, communication between organizations, agency characteristics implementer, socio-economic and political conditions, and disposition. However, there are still some things that need to be paid attention to, such as resource indicators. In terms of resource indicators, the budget owned by the Pinrang Regency government is limited and not sufficient to carry out construction and repair of damaged roads, while the funds needed to carry out road construction are very large.